2010
DOI: 10.1111/j.1872-034x.2010.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 gene promoter polymorphisms affect susceptibility to hepatitis C virus infection and disease progression

Abstract: These results suggest that the -1195GG genotype of the COX-2 promoter region protects against HCV infection in the Japanese. However, once chronic infection is established, the -443TT genotype of the OPN promoter region and the -1195GG genotype of the COX-2 promoter are thought to promote inflammation and contribute to the progression of liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
3
17
2
1
Order By: Relevance
“…In fact, in a recently published study we reported that this polymorphism located at −1195 nucleotides upstream exon 1 increases COX-2 transcriptional activity in two colon cancer cell lines [30]. This was also noticeable in human hepatoma cell lines [31] but antagonizes the increased promoter activity observed for the rs689466 A allele in gastric cancer cell lines [25]. COX-2 overexpression is suggested as one of the smoke-induced pathways involved in carcinogenesis [32], [33].…”
Section: Discussionmentioning
confidence: 75%
“…In fact, in a recently published study we reported that this polymorphism located at −1195 nucleotides upstream exon 1 increases COX-2 transcriptional activity in two colon cancer cell lines [30]. This was also noticeable in human hepatoma cell lines [31] but antagonizes the increased promoter activity observed for the rs689466 A allele in gastric cancer cell lines [25]. COX-2 overexpression is suggested as one of the smoke-induced pathways involved in carcinogenesis [32], [33].…”
Section: Discussionmentioning
confidence: 75%
“…A previous study indicated that the microsatellite polymorphisms of the promoter/enhancer region of FOXP3 were not associated with chronic HCV infection [24], and in our study, we did not receive hepatitis C patients or hepatitis C-related HCC patients, preventing our discussion of FOXP3 gene polymorphisms in HCV infection. Current studies have rarely reported concrete relevance for FOXP3 expression in tumors; the transcript types and biological significance of FOXP3 in cancer remains unclear.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple studies have illustrated that HCV proteins dramatically stimulate COX-2 expression, which is associated with carcinogenesis [9], [32]. To investigate whether the EC isomers could suppress HCV-induced COX-2 expression, we measured the transcription and translation levels of COX-2 in EC-treated Ava5 cells.…”
Section: Resultsmentioning
confidence: 99%